R&D grant and tax credit support for foreign-owned subsidiaries: Does it pay off? - Helena Lenihan; Kevin Mulligan; Justin Doran; Christian Rammer; Olubunmi Ipinnaiye (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Foreign-owned subsidiaries make significant contributions to national Research and Development (R&D) in many host countries. Policymakers often support subsidiaries through R&D grants and R&D tax credits. A key objective of this funding is to leverage R&D-driven firm performance benefits for the host economy. However, the subsidiary's parent firm may decide not to exploit the results from publicly-funded R&D projects in the host country. Therefore, supporting subsidiaries' R&D presents a risk that significant amounts of public funding may translate into little, or no payoffs for the host economy. Our study provides the first evaluation of 1) whether public R&D funding stimulates additional R&D investment in subsidiaries, 2) whether policy-induced R&D drives subsidiary performance, and 3) the differential effects of R&D grants and R&D tax credits. Drawing on a unique panel dataset for Ireland (2007-2016), we find that both R&D supports drive subsidiary R&D, resulting in substantial host country firm performance benefits.
Keywords: D22; O25; F23; F21; O38; D04; H25; O31; 330; Public funding for R&D; Firm performance; Firm ownership; Foreign-owned subsidiaries; Multinational enterprise; R&D tax credit; R&D grant; Policy evaluation